2018
DOI: 10.1159/000489746
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Injection of LKB1 Inhibits the Formation of Diet-Induced Obesity in Rats by Activating the AMPK-POMC Neurons-Sympathetic Nervous System Axis

Abstract: Background/Aims: Obesity is increasingly becoming a major public health problem worldwide. Peripheral LKB1 inhibits white fat generation, but the effect of central LKB1 on diet-induced obesity (DIO) is unknown. Therefore, we examined whether LKB1 over-expression in the hypothalamus can inhibit the development of obesity. Methods: Adult male Sprague-Dawley rats were anesthetized and placed in a stereotaxic apparatus. LKB1-AAV-EGFP (2.0 × 108 or 2.0 × 1010 vector genomes) or Control-AAV-EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Here, we reveal the likely involvement of another kinase cascade, well studied in the contexts of cell growth, metabolism, cancer and polarity ( Shackelford and Shaw, 2009 ) but hitherto unstudied in the context of learning and memory. That this pathway should have a role in learning is perhaps not shocking given the ubiquity of its previously demonstrated roles in 1) axonal development Barnes et al, 2007 ; Shelly et al, 2007 ; 2) synaptic remodeling during aging Samuel et al, 2014 ; 3) regulation of presynaptic neurotransmission Kwon et al, 2016 ; and perhaps most tellingly 4) regulation of glucose metabolism, feeding and obesity through actions in multiple tissues including hypothalamus ( Xi et al, 2018 ; Fei-Wang et al, 2012 ; Claret et al, 2011 ). Given the involvement of hypothalamus in coding of taste palatability, and the connectivity between hypothalamus and gustatory cortex ( Li et al, 2013 ), it is tempting to speculate that the role of Stk11 signaling pathways in feeding may be functionally related to its role in gustatory learning.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reveal the likely involvement of another kinase cascade, well studied in the contexts of cell growth, metabolism, cancer and polarity ( Shackelford and Shaw, 2009 ) but hitherto unstudied in the context of learning and memory. That this pathway should have a role in learning is perhaps not shocking given the ubiquity of its previously demonstrated roles in 1) axonal development Barnes et al, 2007 ; Shelly et al, 2007 ; 2) synaptic remodeling during aging Samuel et al, 2014 ; 3) regulation of presynaptic neurotransmission Kwon et al, 2016 ; and perhaps most tellingly 4) regulation of glucose metabolism, feeding and obesity through actions in multiple tissues including hypothalamus ( Xi et al, 2018 ; Fei-Wang et al, 2012 ; Claret et al, 2011 ). Given the involvement of hypothalamus in coding of taste palatability, and the connectivity between hypothalamus and gustatory cortex ( Li et al, 2013 ), it is tempting to speculate that the role of Stk11 signaling pathways in feeding may be functionally related to its role in gustatory learning.…”
Section: Discussionmentioning
confidence: 99%
“…That this pathway should have a role in learning is perhaps not shocking given its ubiquity and its previously demonstrated roles in axonal specification and dynamics during development (Barnes et al, 2007; Shelly et al, 2007), synaptic remodeling during aging (Samuel et al, 2014), and its ability to regulate axonal function and presynaptic neurotransmission (Kwon et al 2016). In addition, Stk11 and downstream AMP-related kinases have been implicated in regulation of glucose metabolism, feeding and obesity through actions in multiple tissues including hypothalamus (Xi et al, 2018; Fei-Wang et al, 2012; Claret et al, 2011). Given the ability of hypothalamus to encode taste palatability and its connectivity with gustatory cortex (Li et al, 2013), it is tempting to speculate that the role of Stk11 signaling pathways in feeding may be functionally related to its role in gustatory learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the activation of AMPK/SIRT1/LXRα and AMPK/STAT1/STING signaling pathways in macrophages can up-regulate the expressions of ABCA1, ABCG1, and SR-B1, promote intracellular cholesterol outflow, reduce lipid accumulation, and ultimately prevent the occurrence of atherosclerosis ( Lin et al, 2015 ; Cai D. et al, 2021 ). Interestingly, LKB1 is the main upstream kinase of AMPK, so it may participate in cellular lipid metabolism by activating AMPK ( Xi et al, 2018 ). Nevertheless, more evidence is needed to evaluate that macrophage LKB1 participates in intracellular lipid outflow and negatively regulates atherosclerotic plaque formation by activating AMPK/SIRT1/LXR α and AMPK/STAT1/STING signaling pathways ( Figure1 ).…”
Section: Introductionmentioning
confidence: 99%